An Ecological Perspective on Dolomite Formation in Great Salt Lake, Utah - Dunham, Eric C.; Fones, Elizabeth M.; Fang, Yihang; Lindsay, Melody R.; Steuer, Christopher; Fox, Nicholas; Willis, Madelyne; Walsh, Alatna; Colman, Daniel R.; Baxter, Bonnie K.; Lageson, David; Mogk, David; et al. (Frontiers in Earth Science, 2020)
Protodolomite was detected in sediments from Great Salt Lake (GSL), Utah, U.S.A. that have no history of elevated temperature or pressure, conditions that are thought to promote dolomitization of sedimentary carbonates. Protodolomite was abundant in a non-oolitic sediment core from the South Arm (SA) of GSL at <17% salinity but was rare in an oolitic sediment core collected from the North Arm (NA) of GSL at >26% salinity. Protodolomite was also abundant in a non-oolitic NA sediment hand sample yet was absent in a nearby oolitic sediment hand sample in locations that likely receive allochthonous nutrients. Protodolomite was not detected in benthic photosynthetic mats from the SA. However, the mats comprised aragonite with halite and minimal calcite; benthic photosynthetic mats do not form in the NA. To begin to identify potential controls on the formation of protodolomite in the SA and NA of GSL, the composition and abundance of 16S rRNA gene transcripts, carbon cycling activities, and porewater geochemistry of the sediment cores were characterized. Transcripts affiliated with a dominant halophilic, heterotrophic sulfate-reducing bacterium were detected in the uppermost sections of the SA core and their abundance was positively correlated with rates of acetate oxidation/assimilation and concentrations of sulfide. Differences in the quality of organic matter between the SA and NA cores, as indicated by carbon to nitrogen ratios, indicate fresh deposition of photosynthetic biomass at the SA sediment core site but not in the NA sediment core site. Sediment grains from the SA core exhibit micrometer-sized euhedral protodolomite crystals that were not detected in the NA core. Collectively, these observations suggest that deposition of photosynthetic biomass drives the development of a sharp, anoxic lens of heterotrophic sulfate reduction. Sulfide, in turn, may promote dehydration of Mg2+-water complexes and primary protodolomite nucleation and growth. The scarcity of dolomite in the NA sediment core may result from constraints imposed by a combination of extreme hypersalinity and depositional environment on phototrophs and sulfate reducers, their activities, and the thermodynamics of protodolomite formation.